2022
DOI: 10.1007/s00421-022-04927-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of a single bout of stretching or foam rolling on range of motion in healthy adults

Abstract: Purpose Stretching and foam rolling are common warm-up exercises and can acutely increase the range of motion (ROM) of a joint. However, possible differences in the magnitude of change on ROM between these two interventions on the immediate and prolonged effects (e.g., 10 min after the intervention) are not yet well understood. Thus, the purpose of this review was to compare the immediate and prolonged effects of a single bout of foam rolling with a single bout of stretching on ROM in healthy par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…When FR is compared to stretching, meta-analyses show that both treatments are similarly effective in acutely increasing ROM [ 6 ]. However, FR showed more favorable effects compared to stretching on performance parameters, at least under specific circumstances, such as when compared to static stretching, when applied to some selected muscles (i.e., quadriceps, triceps surae) or strength tasks (e.g., maximum voluntary contraction torque), when applied for longer than 60 s, or when the FR included vibration [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When FR is compared to stretching, meta-analyses show that both treatments are similarly effective in acutely increasing ROM [ 6 ]. However, FR showed more favorable effects compared to stretching on performance parameters, at least under specific circumstances, such as when compared to static stretching, when applied to some selected muscles (i.e., quadriceps, triceps surae) or strength tasks (e.g., maximum voluntary contraction torque), when applied for longer than 60 s, or when the FR included vibration [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, FR showed more favorable effects compared to stretching on performance parameters, at least under specific circumstances, such as when compared to static stretching, when applied to some selected muscles (i.e., quadriceps, triceps surae) or strength tasks (e.g., maximum voluntary contraction torque), when applied for longer than 60 s, or when the FR included vibration [ 7 ]. Hence, the authors of theses reviews [ 6 , 7 ] concluded that FR might the better choice as a warm-up, compared to stretching alone (i.e., if performed without a comprehensive warm-up [ 8 , 9 ]).…”
Section: Introductionmentioning
confidence: 99%
“…We suggested that certain joints with more limited ROM such as the ankle or with a prior history of injuries (e.g., sprains) may not be as receptive to foam rolling. Another metaanalysis 9 from our lab revealed no significant ROM differences between single bouts of stretching and foam rolling suggesting they are equally effective. As such, the underlying mechanisms of increased stretch tolerance or soft-tissue compliance would likely be similar for static stretching and foam rolling.…”
Section: Foam Rolling Effects On Range Of Motionmentioning
confidence: 81%
“…FR is a collective term for manual therapy techniques based on the application of mechanical force using a foam roller on soft body tissue. Recent studies have showed that a single FR application can increase the ROM of a joint immediately after the treatment [ 18 , 19 , 20 ] and for durations of up to 30 min post-treatment [ 21 ]. Although an increased ROM is the main effect of FR [ 22 , 23 ], muscular recovery after exercise [ 24 ] and sport performance [ 25 , 26 ] have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, this paper is focused on the effects of foam rolling and not in the comparison between these two techniques. A more recent meta-analysis focused on comparing these two techniques [ 20 ]. This current research reports similar effects on the ROM concerning stretching and FR, but this paper does not divide the results by stretching type.…”
Section: Introductionmentioning
confidence: 99%